First Insight into a Nationwide Genotypic Diversity of Mycobacterium tuberculosis among Previously Treated Pulmonary Tuberculosis Cases in Benin, West Africa - AFFOLABI, DISSOU (My University, 2017)
Background. Molecular studies on tuberculosis (TB) are rare in low-resource countries like Benin, where data on molecular study on previously treated TB cases is unavailable. Materials and Methods. From January to December 2014, all smear- and culture- positive previously treated pulmonary TB patients from all TB clinics were systematically recruited. Drug susceptibility testing and spoligotyping were performed on all isolates. Results. Of the 100 patients recruited, 71 (71.0%) were relapse cases and 24 (24.0%) were failure cases, while 5 (5.0%) were default cases. Resistance rate to any first-line drug was 40.0%, while 12.0% of strains were multidrug-resistant (MDR) and no strain was extensively drug-resistant (XDR). A total of 40 distinct spoligotypes were found to be corresponding to a genotypic diversity of 40.0%. ST61 was the most predominant spoligotype with prevalence of 33.0%. In all, 31 single spoligotypes and nine clusters were observed with 2 to 33 strains per cluster giving a clustering rate of 69.0%. Euro-American (Lineage 4) was the most prevalent lineage (74.0%) and Lineage 2 was associated with resistance to streptomycin. Conclusion. This first insight into genetic diversity of previously treated pulmonary TB patients in Benin showed a relatively high genetic diversity of Mycobacterium tuberculosis.